2019
DOI: 10.26582/k.51.2.15
|View full text |Cite
|
Sign up to set email alerts
|

The effects of positional role on tactical behaviour in a four-a-side small-sided and conditioned soccer game

Abstract: In soccer, different tactical behaviours of individuals are necessary to perform well as a team. The demands put on players from different positional roles can be manipulated in training through small-sided and conditioned games and tactical behaviours might be stimulated. The aim of this study was to assess the effects of positional role in tactical behaviour of U-17 youth soccer players based on core tactical principles in a four-a-side small-sided and conditioned game. The sample was comprised of 268 U-17 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
10
0
3
Order By: Relevance
“…The experimental design comprised a 3 vs. 3 + 1 SSG in two different pitch sizes: 36 x 27 m (~139 m²) and 40 x 29 m (~166 m², ~19% larger). The 36 x 27 m pitch size was extensively adopted in literature (Machado, Padilha, et al, 2019;Sousa, et al, 2019;Teoldo, et al, 2011) and was reported to represent the same proportions of the official pitch to the 3 vs. relative area per player usually adopted in this pitch is 162 m², which has been reproduced in the 40 x 29 m pitch size (~166 m² considering the seven players). Therefore, in the current study, we tested both absolute and relative areas largely adopted in literature.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental design comprised a 3 vs. 3 + 1 SSG in two different pitch sizes: 36 x 27 m (~139 m²) and 40 x 29 m (~166 m², ~19% larger). The 36 x 27 m pitch size was extensively adopted in literature (Machado, Padilha, et al, 2019;Sousa, et al, 2019;Teoldo, et al, 2011) and was reported to represent the same proportions of the official pitch to the 3 vs. relative area per player usually adopted in this pitch is 162 m², which has been reproduced in the 40 x 29 m pitch size (~166 m² considering the seven players). Therefore, in the current study, we tested both absolute and relative areas largely adopted in literature.…”
Section: Methodsmentioning
confidence: 99%
“…The system is used to analyze both technical and tactical behaviors in a video match. FUT-SAT is a tactical assessment system designed specifically for football/soccer that is used by Moreira et al [115] and Machado et al [116]. The system allows for the progression of player movement in the game across all age groups and levels.…”
Section: Software Used To Analyze Performancementioning
confidence: 99%
“…Regarding the development of the decision-making skill, literature highlights the importance of athletes experiencing a great amount of structured sport practice (e.g., team training) throughout their development process (Berry et al, 2008). Besides, it is necessary that much of this time focused on structured practice includes activities that enable the interaction of perceptual-cognitive and technical skills, as through the utilization of small-sided games, which provides a rich environment to foster the players' game reading and decision-making skills (Machado et al, 2017;Machado et al, 2019;. Another characteristic of this component is its straight connection to the tactical dimension of soccer, since every action in the game has a tactical purpose (Garganta, 2009).…”
mentioning
confidence: 99%